ESL Teacher and Student Beliefs and Practices in the Teaching of Oral Communication Skills - Spawa, Clarvie M. Charles (2011)
Poor oral communication proficiency among Malaysian learners has become a national problem. Oral communication skills in ESL is important if Malaysia wants to produce a generation of global communicators which is in line with the country’s mission to become a fully developed nation. However, we often hear of grievances that many of Malaysian graduates are not employed due to their poor communication skills in English. This study seeks to compare between the beliefs and practices in the teaching of ESL speaking skill. The study involved ESL teachers and from different regions in Malaysia. The respondents were chosen using purposive sampling. The major statistical procedures used in the quantitative study were descriptive statistics and paired samples t-tests. Semi structured interviews were analyzed for themes and categories. The results suggest that both teachers believe oral communication skills in English is important in students’ language learning. However, teachers faced numerous challenges in translating this belief into practice. This has led to a discrepancy between in teachers’ beliefs and practice in developing students’ oral communication skills.